Behavioral Biometrics for Healthcare Cybersecurity - McBride, Maurice L.; Young, Kenna L. (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
With patient records going online, healthcare organizations are facing new-age threats and old-world security solutions. Typing, mouse, and voice dynamics are continuous and non-intrusive user authentication, enhancing security in clinical systems. This paper discusses the application of behavioral biometrics in mitigating insider threats, compromised credentials, and unauthorized access in the healthcare sector. The paper utilizes peer-reviewed articles published between 2020 and 2025 and applies thematic analysis to identify patterns, advantages, and disadvantages. Studies reveal that behavioral biometrics enhances identification, reduces system vulnerabilities, and can be easily integrated into existing systems. However, issues remain regarding algorithm bias, user privacy, and the system's sensitivity. The article concludes that while behavioral biometrics cannot be an effective substitute for conventional security measures, they are a valuable addition to IT security in the rapidly growing field of digital healthcare and can help healthcare facilities meet regulatory requirements.